Electro-oxidation of fish meal industry wastewater in a stirred batch reactor using a Ti/RuO2 anode - Raju Meganathan (IWA Publishing, 2021)
Fish meal is used as feed for fish, dogs and cats, and in the pharmaceutical industry. Direct electro-oxidation has been used to treat fish meal industry effluent and organic pollutant removal, and was studied in this project. The anode used was titanium coated with ruthenium oxide and the cathode was stainless steel. In addition to organic pollutants, color removal was also studied. The varying parameter was current density, and those used were 10, 20, 27, and 34 mA/cm2. The effects of mechanical agitation and the inter-electrode distance on pollutant removal were also studied. The highest TOC and color removal (both 82%) were achieved at 34 mA/cm2, using mechanical agitation with 1.5 cm electrode spacing. Without agitation, TOC removal efficiency was 72%. The results show that electro-oxidation can be an effective secondary treatment for fish meal industry effluent. HIGHLIGHTS The electro-oxidation process to treat fish meal industry wastewater has been discussed.; The significance of using a mechanical agitator during the electro-oxidation process has been studied.; The efficiency of Ti/RuO2 anode in removing organic pollutants has been observed using a laboratory-scale batch reactor.; Different parameters such as current densities, inter-electrode spacing, and pH have been discussed in this paper.;